Synthesis of hyper-cross-linked microporous poly(phenylacetylene)s having aldehyde and other groups and their chemisorption and physisorption ability. (May 2019) - Havelková, Lucie; Hašková, Alena; Bashta, Bogdana; Brus, Jiří; Lhotka, Miloslav; Vrbková, Eva; Kindl, Martin; Vyskočilová, Eliška; Sedláček, Jan
Graphical abstract: Highlights: Hyper-cross-linked microporous polyacetylene networks were prepared. High extent of decoration of the networks with CHO or NH2 groups was achieved. Network with CHO groups is highly efficient for selective reversible chemisorption. Network with NH2 groups is an efficient multifunctional physisorbent. Network with NH2 groups catalyses aldol condensation. Abstract: The chain-growth homopolymerization of 3, 5-diethynylbenzaldehyde proceeding through the transformation of the ethynyl groups of the monomer yields hyper-cross-linked poly(3, 5-diethynylbenzaldehyde), P(DEBA), with a high content of carbaldehyde groups (6.5 mmol/g) and specific surface of about 900 m 2 /g. The covalent structure of P(DEBA) consists of polyene (polyacetylene) main chains cross-linked with 5-formyl-1, 3-phenylene links. P(DEBA) selectively and reversibly chemisorbs alcohols and primary amines (capacity up to 350 mg/g) through binding these solutes in the form of acetal and Schiff base type segments, respectively. The condensation of P(DEBA) carbaldehyde groups with amino groups of ethylenediamine (EDA) gives microporous P(DEBA)/EDA2 extensively decorated with base NH2 groups. P(DEBA)/EDA2 is effective for physisorption of ibuprofen solute (capacity, 1130 mg/g) and CO2 gas (capacity, 360 mg/g, 7 bar, 273 K) and is active as a heterogeneous catalyst of aldol condensation of n -heptanal with benzaldehyde to jasminaldehyde.